Pelestarian Nyanyian Baghandu sebagai Budaya Leluhur terhadap Penutur dan Masyarakat di Desa Sungai Liti Kecamatan Kampar Kiri Provinsi Riau - Putri Utami (Journal on Education, 2023)
This research aims to tell others how the preservation and baghandu songs sung by speakers make the ancestral culture for the future. This research includes qualitative research using descriptive methods. This writing technique is carried out by collecting data with a question by way of interviews, recording techniques and other techniques such as listening repeatedly to the speaker's chant and the technique of recording the text that has been sung. The research data is sourced from the sources themselves and various articles and journals. The differences between this study and other studies are in terms of the basic concepts of baghandu, baghandu speakers, baghandu audiences, musical instruments, time and place of performance, and the atmosphere of baghandu performances.